Nonoxidative pentose phosphate pathway regulates CD8 + T cell immunity by maintaining NADPH homeostasis - Jingyu Feng; Qian Zhang; Li Luo; Zhichao Gu; Wen Liu; Jingsong Xu; Mengxin Qi; Zhongji Meng; Lin Li; Liangliang Lin; Zhuoshun Yang; Huafeng Zhang (Proceedings of the National Academy of Sciences, 2026)
NADPH is essential for cellular biosynthesis and redox balance in CD8 + T cells. Here, we demonstrate that the nonoxidative pentose phosphate pathway (non-oxPPP), mediated by transketolase (TKT) and transaldolase (TALDO1), is critical for CD8 + T cell activation, proliferation, and memory formation by maintaining NADPH homeostasis. Metabolomic profiling and isotopic tracing revealed upregulated non-oxPPP flux in effector (T eff ) and memory (T m ) CD8 + T cells, enabling a pentose cycle that amplifies NADPH yield and sustains metabolic fitness for T cell immunity. Genetic knockdown or pharmacological inhibition of Tkt or Taldo1 impaired NADPH production, leading to ribose-5-phosphate (R5P) accumulation, oxidative stress, reduced lipid synthesis, mitochondrial dysfunction, and compromised T eff cell proliferation, cytokine production, and antitumor efficacy. Conversely, enhancing non-oxPPP activity promoted T m differentiation, persistence, and recall responses. Targeting the non-oxPPP represents a promising strategy to enhance cancer immunotherapy and vaccine efficacy by bolstering T cell effector and memory responses.